CREATING CRAFTS TO INCREASE CREATIVITY DURING PANDEMIC - siti indatul laili; Tri Peni; Tri Ratnaningsih (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
Creativity is a trait that dares to break the paradigm so that it can produce something, and can also help children become better at doing various things. The purpose of this study was to prove the effect of making crafts on increasing creativity during the pandemic in students of SMPN 1 Mojoagung Jombang. The design of this study used a one-group pre-post test design. The population in this study were all students of class IX SMPN 1 Mojoagung Jombang as many as 287 students. The sample of this study were all students of class IX F, IX G, IX H, and IX I SMPN 1 Mojoagung Jombang as many as 107 respondents. The sampling technique used is cluster random sampling. The instrument used is a questionnaire to assess creativity with test results 100% valid and reliable with = 0.798. This research was conducted at SMPN 1 Mojoagung Jombang in November 2021. The statistical test used the Wilcoxon Sign Rank test with table = 0.05. The results showed that there was an increase in creativity from 43 (40%) respondents before making crafts. And after making crafts increased to 69 (64%) respondents. Statistical test results = 0.00. it means that there is an effect of making crafts on increasing creativity. Creative thinking is needed to create new ideas in making crafts so that they can produce diverse products. Thus, making handicrafts activities can increase children's creativity.